Trajetórias profissionais de executivas aos postos de alto escalão: fatores-chave, barreiras, inibidores de ascensão e estratégias de enfrentamento - Silva, Rosangela Vianna Alves da (2012)
This research aimed at understanding the career paths of executive women to senior posts, the key factors, barriers and inhibitors ascension faced by them in their tracks, as well as the coping strategies employed. Therefore, we performed a study eminently qualitative which research strategy was based on the method of multiple case study, with the units of analysis focused on the individual level, namely the exploration of professional and life experiences of executives who have reached senior positions. Data were collected through in-depth interviews with 18 professionals who work, or had worked, in the board of national and multinational organizations located in the city of Rio de Janeiro. The research revealed that work is a central source of identity to these women, and that their professional careers, although unique, showed a common pattern: these executive undertook diagonal trajectories, returned over several different organizations, which could be indicative of how they coped with the 'glass ceiling' over their professional development. The survey also revealed that the determinants families, especially mothers, were only identified as barriers to career advancement for executive childless. For executives with children, motherhood was seen as a natural moment of their lives, which required some concessions, but whose potential conflicts were equated so that this dimension of their lives to balance with the ball work for all, is an important source of identity.